Resemanticization of Local Swear Words and Social Limits on Their Use in Interactions among Senior and Vocational High School Students in Makassar City - M. Sayful; Nurliah Nurliah; Abd. Kahar Muzakkir (SIGn Journal of Social Science, 2025)
Local swear words in student interactions serve social functions that extend beyond expressions of anger or verbal attacks. Their functions are shaped by the situation of use, relationships between speakers, the purpose of the utterance, and responses that emerge during interaction. This study examines the forms, contexts, social functions, and limits of resemanticization of local swear words in interactions among senior and vocational high school students in Makassar City. The study employed a descriptive qualitative approach with a case study strategy. Twelve schools were selected through systematic random sampling, while 12 informants were purposively selected. Primary data were collected through in-depth interviews, participant observation, and digital observation and were analyzed by coding elements of speech events and comparing findings across sources. The findings show that swear words function as expressions of emotion and affect, markers of solidarity and social identity, and means of conveying complaints containing elements of resistance to authority. Their use also reveals normative ambivalence because swear words may be accepted among peers but restricted within families and schools. Resemanticization occurs when a change in pragmatic function is accompanied by a change in social meaning without eliminating offensive lexical meaning. These findings demonstrate that swearing is a contextual linguistic practice that reflects students’ ability to adjust their language choices to social relationships and interactional situations.